2021
DOI: 10.3917/reco.pr2.0174
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Adaptation to Climate Change on Farmers’ Income in the Savanna Region of Togo

Abstract: Les ménages agricoles qui prennent des mesures pour s’adapter au changement climatique ont-ils un revenu plus élevé que ceux qui ne le font pas ? Cet article vise à répondre à cette question dans le contexte des revenus des cultures et du bétail dans la région des savanes au Togo. À cette fin, nous construisons un modèle bioéconomique basé sur le modèle de ménage agricole. En utilisant les données d’enquête recueillies auprès d’un échantillon de 450 ménages agricoles au cours de l’année agricole 2012-2013, nou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Larger farm sizes allow higher returns, thereby improving the ability of farmers to engage in other economic ventures in order to diversify their risk (income diversification). This outcome is consistent with similar studies on climate change (Pilo et al 2021, Deressa, 2007, Fosu-Mensah, 2012.…”
Section: Gender Of Head Of Householdsupporting
confidence: 93%
“…Larger farm sizes allow higher returns, thereby improving the ability of farmers to engage in other economic ventures in order to diversify their risk (income diversification). This outcome is consistent with similar studies on climate change (Pilo et al 2021, Deressa, 2007, Fosu-Mensah, 2012.…”
Section: Gender Of Head Of Householdsupporting
confidence: 93%
“…Awoye et al (2017) showed that without appropriate adaptation strategies, pineapple, maize, groundnut, cassava and cowpea will be adversely affected, with an average reduction in yields in the range of 11%-33% by 2050. Adoption of adaptation strategies is therefore crucial to sustain and promote agricultural productivity growth (Roco et al, 2017) as it has the potential to alleviate the adverse effects of climate change and variability and reduce yield losses (IPCC, 2014;Pilo et al, 2021). Many adaptation strategies such as technologies and practices related to soil, water, crop and land risk management are used to adapt to the effects of climate change.…”
Section: Climate Change Adaptation Strategies Efficiencymentioning
confidence: 99%
“…These results imply that the producer suffers a loss when they choose not to adapt. In Togo, Pilo et al (2021) showed that climate change adaptation strategies such as soil and water conservation techniques and irrigation practices can mitigate at least 63% of climate change impacts on farmers' incomes. Ogada et al (2020) showed in Kenya that adoption of multiple stress tolerant crops improves household income by 83%.…”
Section: Climate Change Adaptation Strategies Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…These activities lead to the gradual deterioration of natural ecosystems and the depletion of vital resources, thereby jeopardizing the productive capacity of agricultural systems worldwide. Climate change causes crop damage, low productivity, and high production costs that lead to losses in farmers' income, a high poverty level, high inequality, and finally a reduction in farmers' active involvement (Alalade et al, 2021;Alam et al, 2018;Maja & Ayano, 2021;Pilo et al, 2021;Sallawu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%